THE IMPACT OF GREEN FINANCING MECHANISMS ON THE DEVELOPMENT OF SMALL BUSINESS AND PRIVATE ENTREPRENEURSHIP - Kodirov, Javlonbek Nematullayevich (THE INNOVATION ECONOMY, 2026)
This article analyzes the impact of green financing mechanisms on the development of small businesses and private entrepreneurship. It examines the role of green loans, investments, and other financial instruments in promoting ecological innovations. The study highlights the importance of financial support for green technologies. The results show that effective use of green financing improves competitiveness, energy efficiency, and environmental sustainability.